International Indicators as a Measure of National Policies - Penn, Helen (International journal of early childhood, 2014)
National policies on Early Childhood Care and Education (ECEC) are usually evaluated by commentators in terms of their own history and context. However, the recent OECD family database offers comparative tables on a range of ECEC policies, and charts their impact on different socio-economic groups within countries. From a comparative point of view some measures are clearly more effective than others in redistributing income and mitigating inequality. This article is based on recent work undertaken for the Department of Education in England, and illustrates how analysis of the OECD figures can highlight the strengths and weaknesses of ECEC policy in the UK. It demonstrates that whilst UK expenditure on ECEC services is high, there is a relatively poor return on investment. It suggests in particular that demand-led payments (giving money to parents rather than to services) and loose regulatory requirements about private sector charges and finances, lead to poor value for money.